Penerapan Rebusan Daun Seledri Terhadap Tekanan Darah Pada Penderita Hipertensi - Puspita, Pupi; Utami, Fenasri; Nanda, Sabira Putri; Hanafi, Ahmad Yusran; Pertiwi, Dwi Meyrisca; Wulan, Fitri; Situmorang, Ronalen Br. (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Hypertension is one of the most common health problems and a major risk factor for heart disease, stroke, and kidney failure. It remains one of the most serious public health problems globally. According to World Health Organization (WHO) data, in 2024, approximately 1.4 billion adults aged 30–79 worldwide were living with hypertension—nearly a third of the adult population in that age range. This condition is particularly prevalent in low- and middle-income countries, where two-thirds of those with hypertension reside. In Indonesia, according to a 2023 survey by the Indonesian Ministry of Health (Kemenkes), the prevalence of hypertension among people aged 18 and over was recorded at 30.8%. Efforts to treat hypertension rely not only on pharmacological therapy but also on non-pharmacological interventions such as the use of natural ingredients. One plant widely used in traditional medicine is celery (Apium graveolens), which is known to contain active compounds such as apigenin, flavonoids, and phthalides that play a role in blood vessel dilation and lowering blood pressure. Celery leaf decoction has long been used as a traditional remedy to help control blood pressure, but its use in the community is often not based on a proper understanding of its mechanisms. Therefore, the use of celery leaf decoction as a complementary therapy for hypertension sufferers needs to be studied and implemented more systematically to support safe, effective, and easy-to-administer blood pressure management using affordable ingredients.